Sustaintabilitas Agribisnis Urban Farming: Potret Hidroponik Plant Quarter Banda Aceh - Virda Zikria; Nasrullah Nasrullah; Noratun Juliaviani; Elly Susanti (Jurnal Agrisep, 2026)
Hydroponic farming is one form of urban horticultural agribusiness that has emerged in response to limited agricultural land and the increasing demand for healthy and high-quality food products. This study aims to analyze the financial feasibility, business model, and sustainability level of the hydroponic enterprise Plant Quarter in Banda Aceh City. The research employed a case study method, with data collected through interviews, observations, and documentation. Data analysis was conducted using financial analysis, the Business Model Canvas (BMC) was utilized to identify the business model based on its nine key elements, while sustainability analysis was carried out using the Composite Sustainability Index (CSI), which encompasses economic, social, and environmental dimensions. The results indicate that Plant Quarter generates a total monthly revenue of IDR 6,000,000 with a total monthly cost of IDR 2,853,750, resulting in a monthly profit of IDR 3,146,250. The R/C Ratio of 2.10 demonstrates that the business is financially feasible, while the ROI of 11.60% and a Payback Period of 8.62 months indicate a relatively rapid investment recovery. The Business Model Canvas analysis reveals that the main strengths of the enterprise lie in product quality, educational functions, and diverse customer segments, whereas the primary challenges include limited production capacity and suboptimal utilization of digital marketing. The sustainability analysis shows an economic index of 100, a social index of 92, and an environmental index of 92, resulting in a Composite Sustainability Index of 94.67, which falls within the highly sustainable category. These findings suggest that Plant Quarter has strong potential to serve as a sustainable urban horticultural agribusiness model in Banda Aceh City.